Population pharmacokinetic assessment of a new regimen of mefloquine used in combination treatment of uncomplicated falciparum malaria. - Ashley, E; Stepniewska, K; Lindegårdh, N; Mcgready, R; Hutagalung, R; Hae, R; Singhasivanon, P; White, N; Nosten, F (2006)
A fixed artesunate-mefloquine combination, comprising three daily doses of 8 mg of mefloquine/kg of body weight and 4 mg of artesunate/kg, has been developed recently. This study was designed to construct a population pharmacokinetic model describing this new dosage regimen of mefloquine given as loose tablets together with artesunate. In two randomized trials in Thailand which evaluated the efficacy, safety, and tolerability of this new regimen, the members of a subgroup of 50 patients were randomized to have capillary blood sampling before treatment and at five randomly assigned time points during the 63-day follow-up period. Mefloquine levels in capillary whole blood were assayed by liquid chromatography with UV detection. A pharmacokinetic model for mefloquine was constructed using mixed-effects modeling. A one-compartment model with first-order absorption and elimination was selected to describe the kinetic properties of mefloquine. For capillary whole-blood mefloquine, the area under the concentration curve (AUC) was 40% higher than previous estimates for patients given the equivalent conventional-dose regimen (mefloquine given as 15 mg/kg and then 10 mg/kg on the second and third days of treatment). The half-life (t1/2) of the carboxylic acid metabolite was estimated as 26 days, and the metabolite was eliminated more slowly than the parent drug (population t1/2 estimate, 10.5 days). Splitting the 25 mg/kg dose of mefloquine into three doses of 8 mg/kg each resulted in improved oral bioavailability compared to the conventional split-dose regimen results. This new regimen is well tolerated and results in an equivalent therapeutic response.